ANALISIS KINERJA KARYAWAN GRAGE HOTEL HORIZON BENGKULU - Furqonti Ranidiah; Tezar Arianto (Jurnal Ilmiah Akuntansi, Manajemen dan Ekonomi Islam (JAM-EKIS), 2023)
The purpose of this study was to determine the performance of employees of Grage Hotel Horizon Bengkulu which was assessed based on employee perceptions with the aspects assessed were quality of work, quantity of work, attendance, responsibility, punctuality, and cooperation. This research is a type of qualitative descriptive research. Respondents in this study were 47 employees (as questionnaire fillers), 2 hotel managers, and 2 hotel guests (as interview samples). Data analysis method used descriptive analysis with the help of frequency distribution tables, averages and percentages. From the results of field research and data analysis, the following results were obtained: (1) In general, employee performance, quality of employee work, quantity of employee work, employee attendance rate, employee responsibility level, employee work punctuality, Grage Horizon Hotel employee cooperation ability Bengkulu has good criteria.